2015
DOI: 10.1016/j.beth.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Attention to Nonemotional Distractors Influences State Anxiety: A Proof-of-Concept Study in Low- and High-Anxious College Students

Abstract: Anxious individuals have difficulty inhibiting attention to salient, but nonemotional, distracting stimuli. The exact nature of this relationship remains unclear, however. In the present study, we tested the hypothesis that increasing attention to salient, but nonemotional, distracting stimuli would lead to increases in state anxiety by manipulating attentional strategies during a visual search task. We randomly assigned students low and high in trait anxiety to either a 1-session singleton detection training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…It can include two types of behavioral symptoms, namely state anxiety and trait anxiety. [22,23] In our study, we found a weak and statistically significant relationship in the same direction between prenatal STAI 1 and STAI 2 test scores. This is consistent with the literature confirming that individuals with anxious personality traits respond to immediate situations with strong anxiety.…”
Section: Anxiety-postpartum Depression (Ppd) Level Of the Participantssupporting
confidence: 50%
“…It can include two types of behavioral symptoms, namely state anxiety and trait anxiety. [22,23] In our study, we found a weak and statistically significant relationship in the same direction between prenatal STAI 1 and STAI 2 test scores. This is consistent with the literature confirming that individuals with anxious personality traits respond to immediate situations with strong anxiety.…”
Section: Anxiety-postpartum Depression (Ppd) Level Of the Participantssupporting
confidence: 50%